2013
DOI: 10.1111/ddg.12067_suppl
|View full text |Cite
|
Sign up to set email alerts
|

Depression bei Patienten mit Acne inversa – eine häufige Komorbidität

Abstract: Patients with AI have a higher risk of developing depression. Physicians should be alert to the possible development of depression when treating patients with this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 40 publications
0
2
0
2
Order By: Relevance
“…11 Considering the impairment of quality of life that arises even with moderate disease severity, as well as the significant proportion of HS patients who additionally suffer from depression due to their condition, this timeframe must be shortened for the benefit of patients. [14][15][16][17][18][19] To achieve this, the causes of the diagnos- tic delay must be understood, and potential improvements identified. 20 For this investigation, public internet posts from patients with HS were analyzed to better understand the patient pathway and experience beyond traditional clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Considering the impairment of quality of life that arises even with moderate disease severity, as well as the significant proportion of HS patients who additionally suffer from depression due to their condition, this timeframe must be shortened for the benefit of patients. [14][15][16][17][18][19] To achieve this, the causes of the diagnos- tic delay must be understood, and potential improvements identified. 20 For this investigation, public internet posts from patients with HS were analyzed to better understand the patient pathway and experience beyond traditional clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has revealed that it takes an average of ten years from the onset of the first symptoms of HS to the correct diagnosis 11 . Considering the impairment of quality of life that arises even with moderate disease severity, as well as the significant proportion of HS patients who additionally suffer from depression due to their condition, this timeframe must be shortened for the benefit of patients 14–19 . To achieve this, the causes of the diagnostic delay must be understood, and potential improvements identified 20 .…”
Section: Discussionmentioning
confidence: 99%
“…11 Betrachtet man die Beeinträchtigung der Lebensqualität, die bereits bei einer moderaten Krankheitsausprägung entsteht, sowie den großen Anteil an Patienten mit HS, die aufgrund ihrer Erkrankung zusätzlich an einer Depression leiden, muss diese Zeitspanne zum Wohle der Patienten verkürzt werden. [14][15][16][17][18][19] Dazu müssen die Ursachen für diese Diagnoseverzögerung verstanden und mögliche Verbesse-rungen identifiziert werden. 20 Für die Untersuchung wurden dazu öffentliche Internet-Beiträge von Patienten mit HS analysiert, um abseits klassischer klinischer Studien die Patientenwege der Betroffenen besser nachzuvollziehen.…”
Section: Diskussionunclassified
“…Aktuelle Forschungsarbeiten konnten zeigen, dass vom Auftreten der ersten Symptome der HS bis zur korrekten Diagnosestellung durchschnittlich zehn Jahre vergehen 11 . Betrachtet man die Beeinträchtigung der Lebensqualität, die bereits bei einer moderaten Krankheitsausprägung entsteht, sowie den großen Anteil an Patienten mit HS, die aufgrund ihrer Erkrankung zusätzlich an einer Depression leiden, muss diese Zeitspanne zum Wohle der Patienten verkürzt werden 14–19 . Dazu müssen die Ursachen für diese Diagnoseverzögerung verstanden und mögliche Verbesserungen identifiziert werden 20 .…”
Section: Diskussionunclassified